A judicialização na educação infantil entre ênfases, encaminhamentos e solicitações no município de Sorocaba/SP - Silva, Petula Ramanauskas Santorum e (Universidade Federal de São Carlos, 2018)
The objective of this study was to analyze the legislative process among emphases, referrals, and requests in early childhood education in the city of Sorocaba, São Paulo. The study considers the constraints and limits placed on the rights of the child, from the perspective of day care directors, and focuses particularly on full-day centers. The choice of respondents for the study was a function of their role in the implementation of policy, in addition to their responsibility for administrative and pedagogical dialogue within their day care. The study included interviews of ten full-day day care directors, out of 20 that were invited, based on their willingness to participate in the research. The methodology employed both a qualitative approach as well as data analysis established by studying content from the works of Bardin (2011), Franco (2005), and Campos (2004). The data collection instruments consisted of: 1) a characterization of interview participants, highlighting their attributes and roles regarding the scope of early childhood education for children zero to three years of age in full-day municipal day care centers in Sorocaba, and 2) a questionnaire for day care directors in Sorocaba regarding policy implementation for early childhood education. The theoretical framework of the study was based on a survey of master theses and doctoral dissertations from the Capes platform and on articles from the Scielo platform, none of which were ranked according to their Qualis. The study reviewed literature in the area of education and law between the years 2004 and 2016. Regulation and legal guidelines from the city of Sorocaba -namely the Unified Municipal Register – CMU (SOROCABA / SP, 2017b) and listings of vacancies requested by judicial order (SOROCABA / SP, 2018d) - also contributed to the discussion. The study found that the lack of supply of early childhood education for children zero to three years old in Sorocaba is on one hand due to a lack of dialogue between the executive power (the mayor’s office) and the demands of the population, and a lack of planning and organization for the given age range under study—both factors that deprive the child of his or her right to education. On the other hand, certain legislation has raised issues that affect not only the pedagogical, structural, and human resource organization of day cares, but also the path and historical context of early childhood education in Brazil. The study confirms that the educational right of the child is not currently planned nor fulfilled, and this scenario is expected to continue until the city makes a decision for reform.
The judicialization in early childhood education between emphases, referrals and requests in the city of Sorocaba / SP
Keywords: Judicialização; Educação infantil; Sorocaba-SP; Políticas públicas para educação infantil; Judicialization; Children's education; Sorocaba-SP; Public policies for Children's education; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL